Caregiver Preferences regarding Technology's Role in Supporting Adolescent Weight Management. (26th November 2015) - Bianchi-Hayes, Josette M.; Schoenfeld, Elinor R.; Cataldo, Rosa; Huang, Jiayu; Pati, Susmita
Abstract : Background . Health technology provides a wealth of strategies to address chronic health issues, such as childhood obesity. Few studies have assessed parental preferences regarding use of health technology to support weight management for adolescents. Objective . This study determined caregiver beliefs, attitudes, and practices towards using traditional methods and technology-based health applications to address weight management among overweight adolescents. Methods . Self-administered surveys were distributed to caregivers of children ages 11–18 years in Stony Brook Children's Hospital outpatient offices with a BMI ≥ 85th percentile for age, gender. The data were entered into StudyTrax research platform and analyzed using SAS. Results .  N = 114 . Mean BMI z -score = 1.95 ± 0.50. Two-thirds (65.8%) of caregivers preferred a weight management program that includes both traditional and technology components. Most parents rated involvement in program development (68.1%), access to content (72.4%) as very important. Those who believed their child's weight was a problem( p = 0.01 ) were more likely than other parents to prefer a program that combined both traditional and technology components. Conclusions . Parents' perceptions of their child's weight drove preferences about incorporating technology elements into a weight management program. Future weight management programs should incorporate parental content preferences and be tailored to different age groups.